Facile preparation of iron oxide doped Fe-MOFs-MW as robust peroxydisulfate catalyst for emerging pollutants degradation. (September 2020) - Wan, Yongjie; Wan, Jinquan; Zhao, Joe R.; Wang, Yan; Luo, Ting; Yang, Shou; Liu, Yaxin
Abstract: A novel catalyst (Fe-MOFs-MW) was facilely synthesized under microwave-assisted with NaOH as modulator for activating peroxydisulfate (PDS). The accelerated nucleation process was confirmed by Johnson-Mehl-Avrami (JMA) model. There were abundant reactive sites on prepared Fe-MOFs-MW while maintaining high Space-Time-Yield value up to 2300 kg/m 3 ·d. Degradation performance of Fe-MOFs-MW as PDS catalyst on sulfamethoxazole (SMX) removal was evaluated. Results indicated that Fe-MOFs-MW with more Fe element anchored (10%) exhibited excellent catalytic capacity for PDS. Besides, the fantastic stability and reusability were confirmed through recycle experiment. After recycled for 4 times, the removal efficiency of SMX and TOC was 88% and 31.3% compared to 98% and 38% without recycling, respectively. An accurate prediction model on the degradation effect with water matrices coexisted was established by response surface methodology (RSM) method. Moreover, SO4 ·-, O2 ·- and ·OH were confirmed as the main reactive species through chemical quenching and EPR tests. The mechanism of Fe-MOFs-MW/PDS process mainly based on electron circulation theory was proposed. As the robust PDS catalyst, facile prepared Fe-MOFs-MW was promising in the treatment of emerging pollutants. Highlights: Microwave with modulator synthesis meets the requirements of green-macro synthesis. The JMA model confirms the role of NaOH as the modifier in accelerating nucleation. Fe-MOFs-MW is rich in unsaturated metal sites with hollow tubular morphology. Fe-MOFs-MW/PDS system shows excellent performance for SMX degradation. The prediction model of water matrices on SMX removal is established by RSM model.